2011
DOI: 10.1002/jsfa.4540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adaptive neuro‐fuzzy inference system and artificial neural networks for estimation of oxidation parameters of sunflower oil added with some natural byproduct extracts

Abstract: Incorporation of different natural byproduct extracts into sunflower oil provided an important retardation in oxidation during storage. Effective predictive models were constructed for the estimation of oxidation parameters using ANFIS and ANN modeling techniques. These models can be used to predict oxidative parameter values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…According to results of present study ANFIS is better predict the fatty acid composition of the oils than ANN. These results are in agreement with those reported by previous studies 37, 38.…”
Section: Resultssupporting
confidence: 94%
“…According to results of present study ANFIS is better predict the fatty acid composition of the oils than ANN. These results are in agreement with those reported by previous studies 37, 38.…”
Section: Resultssupporting
confidence: 94%
“…Network parameters include arranged fuzzy membership functions and weight parameters of neural networks to minimize the mean squared error ( MSE ) between the model's output (predicted values) and experimental values and/or to maximize the relationship ( R 2 ) between those two variables through the training phase. Recently, some scientists have attempted to provide various models for the prediction of the qualitative parameters of the extracted oils, for instance researchers compared ANFIS and Artificial Neural Network (ANN) tools in prediction of the stability of sunflower oil enriched by bioactive compounds against deterioration (Karman, Ozturk, Yalcin, Kayacier, & Sagdic, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that oxidation parameters could be successfully predicted using the ANFIS model. Karaman et al also compared the ANFIS and ANN for estimation of oxidation parameters of sunflower oil added with apple pomace, orange peel and potato peel as natural byproduct research. The results indicated that the ANFIS model with a high coefficient of determination ( R 2 = 0.999) had better performance compared to ANN ( R 2 = 0.89).…”
Section: Introductionmentioning
confidence: 99%